1991
DOI: 10.1073/pnas.88.10.4215
|View full text |Cite
|
Sign up to set email alerts
|

Single type-2 astrocytes show multiple independent sites of Ca2+ signaling in response to histamine.

Abstract: MATERIALS AND METHODSPreparation of Cell Cultures. Primary cultures of type-2 astrocytes were prepared from the cerebrum, where dense histaminergic fibers distribute in the brain (18,19), as reported previously (20). Newborn Wistar rats were killed by decapitation. The cerebral hemispheres were collected in Joklik's modified minimum essential medium (MEM) under sterile conditions and the meninges were carefully removed using an operation microscope. The cerebral hemispheres were triturated mechanically with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 39 publications
5
31
0
Order By: Relevance
“…Several studies have shown the existence of histamine H 1 receptors on cultured astrocytes. [39][40][41] More recent studies have shown that astrocytes have histamine H 1 receptors in situ. 42 The most prominent neuropathologic feature of HE is the alteration of astrocyte morphology and function.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the existence of histamine H 1 receptors on cultured astrocytes. [39][40][41] More recent studies have shown that astrocytes have histamine H 1 receptors in situ. 42 The most prominent neuropathologic feature of HE is the alteration of astrocyte morphology and function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the existence of CaMKII in astrocytes (26,28), and CaMKII activated by Ca 2ϩ was shown to phosphorylate vimentin in these cells (19,26). Furthermore, they display local and global Ca 2ϩ signaling in response to neurotransmitters (8,29 (Fig. 1, G-J).…”
Section: Spatial Signaling From Ca 2ϩ Via Camkii To Vimentinmentioning
confidence: 99%
“…[Ca 2ϩ ] i Measurements-The [Ca 2ϩ ] i of cultured astrocytes was measured as described elsewhere (8,24). Briefly, the cells were incubated…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations